The influence of heavy metals and water parameters on the composition and abundance of water bugs (insecta: hemiptera) in the Kerian River Basin, Perak, Malaysia - Mohd Ishadi, Nor Adibah; Md Rawi, Che Salmah; Ahmad, Abu Hassan; Abdul, Nurul Huda (Penerbit USM, 2014)
The hemipteran (Insecta) diversity in the upper part of the Kerian River Basin was low with only 8 families and 16 genera recorded at 4 study sites from 3 rivers. Water bug composition varied among sampling sites (Kruskal-Wallis χ² = 0.00, p<0.05) but was not affected by wet-dry seasons (Z = 0.00, p>0.05). All recorded water parameters were weakly associated with generic abundance but the biochemical oxygen demand (BOD), chemical oxygen demand (COD), Water Quality Index (WQI) and heavy metals (zinc and manganese) showed relatively strong positive or negative relations with hemipteran diversity and richness (H’ and R2). Within the ranges of measured water parameters, the WQI was negatively associated with hemipteran diversity and richness, implying the tolerance of the water bugs to the level of pollution encountered in the river basin. Based on its highest abundance and occurrence (ISI), Rhagovelia was the most important genus and along with Rheumatogonus and Paraplea, these genera were common at all study sites. In conclusion, habitat availability and suitability together with some environmental parameters influenced the abundance and composition of hemipterans in this river basin.